MRI of Temporomandibular Joint Disorders: Recent Advances and Future Directions. Issue 4 (31st August 2020) - Xiong, Xin; Ye, Zheng; Tang, Hehan; Wei, Yi; Nie, Lisha; Wei, Xiaocheng; Liu, Yang; Song, Bin
Abstract : Temporomandibular joint disorders (TMDs) are a prevalent disease covering pain and dysfunction of temporomandibular joints and masticatory muscles, which can be detrimental to quality of life. Magnetic resonance imaging (MRI) is a powerful and noninvasive tool for the imaging and understanding of TMD. With the recent technical development of dynamic and quantitative MRI techniques, including diffusion‐weighted imaging, T2 mapping, and ultrashort/zero echo time, it is now feasible in TMD imaging and has been preliminarily investigated with promising results. In this review we will discuss the recent advances of MRI techniques in TMD and its future directions, and hope to highlight the scientific potential and clinical value of novel MRI techniques in diagnosing and treating TMD. Level of Evidence: 4 Technical Efficacy Stage: 3